An interval Kalman filter enhanced by lowering the covariance matrix upper bound - Tran, Tuan Anh; Jauberthie, Carine; Trave-Massuyés, Louise; Lu, Quoc Hung (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a variance upper bound based interval Kalman filter that enhances the interval Kalman filter based on the same principle proposed by Tran et al. (2017) for uncertain discrete time linear models. The systems under consideration are subject to bounded parameter uncertainties not only in the state and observation matrices, but also in the covariance matrices of the Gaussian noises.
Keywords: uncertain linear systems; Kalman filters; interval analysis; estimation; covariance matrix